1998
DOI: 10.1046/j.1365-2141.1998.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator in acute myeloid leukaemic marrows: u‐PA in contrast to t‐PA in normal marrow

Abstract: Leukaemic and normal bone marrow samples were compared in terms of their content of the fibrinolytic agents, tissue plasminogen activator (t‐PA) and urokinase‐type plasminogen activator (u‐PA) and their inhibitors, plasminogen activator inhibitors 1 and 2 (PAI‐1 and PAI‐2). Normal marrow contained t‐PA as the principal plasminogen activator, whereas in leukaemic marrow samples u‐PA was the predominant activator. Both normal and leukaemic marrows contained PAI‐1 in similar amounts, but whereas normal marrow con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…These findings suggested a major fibrinolytic component to the bleeding disorder, discrete from intravascular coagulation with so-called`secondary' fibrinolysis, that, in our experience, is usually tissue (t)-PArelated (Bennett et al, 1990). It has subsequently been demonstrated that normal bone marrow possesses considerable plasminogen-activating activity, largely because of t-PA (McWilliam et al, 1996), whereas marrow from patients with myeloid forms of acute leukaemia contains u-PA detectable both functionally and immunologically (McWilliam et al, 1998). Scherrer et al (1999) have confirmed the finding of u-PA antigen in leukaemic cells and have shown that they contain the u-PA receptor, u-PAR, in addition.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…These findings suggested a major fibrinolytic component to the bleeding disorder, discrete from intravascular coagulation with so-called`secondary' fibrinolysis, that, in our experience, is usually tissue (t)-PArelated (Bennett et al, 1990). It has subsequently been demonstrated that normal bone marrow possesses considerable plasminogen-activating activity, largely because of t-PA (McWilliam et al, 1996), whereas marrow from patients with myeloid forms of acute leukaemia contains u-PA detectable both functionally and immunologically (McWilliam et al, 1998). Scherrer et al (1999) have confirmed the finding of u-PA antigen in leukaemic cells and have shown that they contain the u-PA receptor, u-PAR, in addition.…”
supporting
confidence: 52%
“…In contrast, procoagulant pathways were relatively normal and anti-thrombin levels were not depleted. We subsequently showed that, in the marrow of normal individuals, there were significant amounts of t-PA activity present, whereas in the marrow from patients with acute myeloid leukaemia, the PA was not t-PA, but u-PA (McWilliam et al, 1996(McWilliam et al, , 1998. Scherrer et al (1999) have recently shown that blast cells in acute myeloid leukaemia contain mRNAs for not only u-PA, but, in some types, for u-PAR, PAI-1 and PAI-2 also.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been demonstrated that the predominant PA activity expressed on the surface of acute leukaemia cells freshly isolated from patients is due to uPA, whereas mononuclear cells isolated from the peripheral blood of patients with chronic leukaemias and healthy individuals were found to be negative for uPA (Tapiovaara et al, 1993). Comparison of normal and leukaemic marrow samples for PA revealed that the principal PA detected in normal marrow is tPA, whereas uPA is the predominant PA in leukaemic marrow (McWilliam et al, 1998). Another study (Wada et al, 1993), based on examination of various leukaemic cell homogenates, showed that both PA and PAI levels are higher in non-lymphoblastic than in lymphoblastic leukaemia.…”
mentioning
confidence: 99%
“…We therefore analysed samples from 37 patients with acute leukaemia at initial presentation for uPA, tPA, uPAR, PAI‐1 and PAI‐2 mRNA expression as well as for uPA and tPA enzymatic activities. Although previous studies have shown either the ability of leukaemic cells to produce PA in cell culture conditions (Wilson et al , 1983) or that PA activity is associated with the leukaemic cells (Tapiovaara et al , 1993; Wada et al , 1993; MacWilliam et al , 1998), we found it of interest to combine both approaches by studying PAs activity associated with leukaemic cells as well as the activity of PAs released by leukaemic cells. This combined approach has been completed by analyses of mRNA expression of PA system components.…”
mentioning
confidence: 99%